A prerequisite to L1 homophone effects in L2 spoken-word recognition. (January 2015) - Nakai, Satsuki; Lindsay, Shane; Ota, Mitsuhiko
When both members of a phonemic contrast in L2 (second language) are perceptually mapped to a single phoneme in one's L1 (first language), L2 words containing a member of that contrast can spuriously activate L2 words in spoken-word recognition. For example, upon hearing cattle, Dutch speakers of English are reported to experience activation of kettle, as L1 Dutch speakers perceptually map the vowel in the two English words to a single vowel phoneme in their L1. In an auditory word-learning experiment using Greek and Japanese speakers of English, we asked whether such cross-lexical activation in L2 spoken-word recognition necessarily involves inaccurate perception by the L2 listeners, or can also arise from interference from L1 phonology at an abstract level, independent of the listeners' phonetic processing abilities. Results suggest that spurious activation of L2 words containing L2-specific contrasts in spoken-word recognition is contingent on the L2 listeners' inadequate phonetic processing abilities.